A new synonym of Neomida luteonotata (Pic, 1926) (Coleoptera: Tenebrionidae: Diaperini) - Aloquio, Sergio (2017)
The genus Neomida Latreille, 1829 (Tenebrionidae: Diaperini) comprises 42 species in the New World (Triplehorn, 2006). Species from America north of Colombia have been recently revised in detail by Triplehorn (2006), who additionally provided general notes on other New World representatives. One of these taxa was Neomida luteonotata (Pic, 1926). This species is easily recognized among its congeners by the unique elytral coloration, which consists of a large shield-shaped black spot in the middle and yellowish to reddish brown area around it. The area of the elytra covered by the median spot is highly variable within a single population. In some individuals it reaches the elytral sides, confining the light area to the bottom and apex of elytra. Hoplocephala luteonotata was described by Pic (1926) based on a single specimen labelled “Brasilia meridionalis”. In 2006, Triplehorn transferred it to the genus Neomida. In the same paper, he synonymized Hoplocephala huedepohli Kulzer, 1961 with N. luteonotata. While working on his publication, Triplehorn had access to Pic’s holotype, but not to the holotype of H. huedepohli, therefore he proposed the above mentioned synonymy partly based on literature resources. Triplehorn (2006) also noted that Hoplocephala atricollis Kulzer, 1961 is probably another junior synonym of N. luteonotata. However, he didn’t have access to the holotype of H. atricollis and the information provided in the original description was insufficient for him to officially propose this synonymy. The present investigation of the types of Hoplocephala huedepohli (Figs. 1–2) and H.